Understanding Barriers and Motivators of Familial Hypercholesterolemia Genetic Testing: Insights From the Singapore Public - Dorothy S. R. Quek; Ruoyu Yin; Frederick H. F. Chan; Ashna Nastar; Joanne Ngeow; Sharon Pek; Julian Savulescu; Tavintharan Subramaniam; Konstadina Griva (Journal of Genetic Counseling, 2026)
ABSTRACT Familial hypercholesterolemia (FH) is a common monogenic disorder associated with elevated low‐density lipoprotein cholesterol and premature cardiovascular disease. Despite Singapore's high FH prevalence and the launch of the National FH Genetic Testing Programme in 2025, uptake remains suboptimal. This study aimed to assess public attitudes, perceptions, and willingness to undergo FH genetic testing. A cross‐sectional survey of 333 Singaporean adults was conducted. Descriptive and comparative analyses assessed willingness, concerns, and information needs. While 71% of participants expressed some willingness to test, only 25% reported strong intention. Individuals who were ‘somewhat willing’ exhibited aversion levels similar to those ‘unwilling’, reflecting ambivalence and a risk of inaction without targeted support. Insurance coverage increased willingness, whereas encouragement from health professionals or family had minimal effect. Participants with high cholesterol were more willing to test than those with normal cholesterol. Key barriers for individuals with normal and high cholesterol included concerns about cost, insurability, data privacy, emotional readiness, and perceived necessity. Information needs varied by willingness level, with those more willing prioritizing practical and logistical details while ambivalent or unwilling participants needed guidance on benefits and costs, post‐test pathways, and data protection. Financial subsidies alone are insufficient to maximize uptake. Tailored communication and decision support interventions from healthcare providers addressing psychosocial and information barriers are essential to support effective implementation of national FH genetic testing programs.